REVITALIZING ARABIC VOCABULARY LEARNING THROUGH THE USE OF AUGMENTED REALITY MEDIA - Haryati, Ratih; Salamah, Ummu (Kitaba, 2024)
This research is a qualitative study using library research aimed at examining and analyzing Augmented Reality (AR) technology as a form of revitalization in the teaching of Arabic mufradat. The data generated in this research are qualitative, involving information in the form of words, sentences, and opinions, rather than numerical data. The data analysis technique in this study uses content analysis method. The validity of the data is ensured through the technique of source triangulation, which involves testing the validity of the data by cross-checking the information obtained from various literature sources. The research results indicate that the use of Augmented Reality (AR) as a form of revitalization in the teaching of Arabic mufradat creates a significant innovation to enhance the quality of learning. Through AR, learners can experience interactive, dynamic, and comprehensive learning, motivating them to explore further in understanding mufradat effectively. The three-dimensional visualization benefits of mufradat, contextual learning, and flexible access to materials through AR have a positive impact on the understanding of linguistic concepts, accelerate Arabic language learning, and bridge the gap between theory and practice.